Reoperation for persistent or recurrent secondary hyperparathyroidism - Abruzzo, Alida; Gioviale, Maria Concetta; Damiano, Giuseppe; Palumbo, Vincenzo Davide; Buscemi, Salvatore; Lo Monte, Giulia; Gulotta, Leonardo; Buscemi, Giuseppe; Lo Monte, Attilio Ignazio (Acta Biomedica Atenei Parmensis, 2017)
Background: Secondary hyperparathyroidism is a common acquired disorder seen in chronic renal failure. Its pathophysiology is mainly due to hyperphosphatemia and vitamin D deficiency and resistance. When medical treatment fails, subtotal and total parathyroidectomy with autotransplantation are the standard procedures, although both are associated with high recurrence rates. Methods and Results: 4 patients experienced persistence and 9 relapse. The first 4 were subjected to reoperation after 6 months for the persistence of symptoms due to the finding of a supernumerary adenomatous gland while the remaining patients at the reoperation showed in 5 cases 2 more glands in over thymic position, and 4 an hyperplasia of the residual glandular tissue. A classic cervicotomy was sufficient to remove the residual parathyroid in patients with persistent hyperparathyroidism. For cases of recurrent hyperparathyroidism it was enough a medial approach and sometimes lateral for the complete excision of the hyperplastic tissue. The advent of the intraoperative technique of parathyroid hormone dosage allowed a better performance of the surgical technique for the last 3 patients undergoing reoperation. After reoperation all patients had immediate regression of clinical symptoms with normalization of serum calcium and PTH levels. Conclusions: On the basis of these considerations, diagnostic imaging has a not negligible role because during the first intervention helps to have an idea of the possible location of the glands and thus to avoid the risk of recurrence and relapse due to ectopic or supernumerary tissue.